A method for preparing an alloy hollow micro-lattice material with gradient composition ratio
By depositing multiple metal layers on a hollow metal lattice material template and then performing heat treatment, a multi-purpose hollow metal lattice material was prepared, realizing gradient design, solving the problem of material composition ratio design, and expanding the application range and performance.
Patent Information
- Application Number
- CN202411209217.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-12-09
- Estimated Expiration
- 2044-08-30
AI Technical Summary
How to achieve gradient composition ratio design of metal hollow microlattice materials to meet the needs of future diversified and integrated applications.
Multilayer metal layers are deposited on a metal hollow microlattice material template using surface deposition technology, and then thermally diffused alloying is used to prepare alloy hollow microlattice materials with gradient composition ratios. The specific steps include surface pretreatment, multilayer metal layer deposition, and thermally diffused alloying.
The gradient alloying design goal of hollow metal microlattice materials has been achieved, expanding the material properties and application range. It is simple to operate, safe and reliable, environmentally friendly, and its elemental composition is flexible and controllable, making it suitable for complex structures.
Smart Images

Figure CN119082810B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of metal hollow micro-lattice preparation, in particular to a preparation method of an alloy hollow micro-lattice material with gradient component proportion. BACKGROUND
[0002] The metal hollow micro-lattice material has excellent properties such as low apparent density and high specific strength, and its structure is simple and can be designed, so it is one of the new lightweight materials with super strength and super lightness. The material science research three elements (material design, structure design and function design) are integrated into one, and it has strong designability. The composition of the material is a series of hollow metal tubes connected by nodes according to a certain structural relationship. In the face of this complex structure, the chemical plating process is used as a means of material design to cope with the complexity of the structure and obtain a complete structure tube wall.
[0003] At present, the alloy material of multi-component alloying has become one of the important design targets of the material design of the metal hollow micro-lattice material. The equimolar ratio of multi-main element alloy, that is, high-entropy alloy, has unprecedented advantages, and has excellent properties such as high strength, high hardness, high wear resistance, excellent oxidation resistance and corrosion resistance. Through multi-level deposition and thermal diffusion alloying, it can be successfully applied to the material design of the metal hollow micro-lattice material, which greatly expands the material design, material performance and application space of the metal hollow micro-lattice material.
[0004] With the in-depth development of the multi-element integrated design of the metal hollow micro-lattice material, the application of the material in the future will have the use demand of facing the ladder type condition. According to the design characteristics of the metal hollow micro-lattice material, how to realize the design of the alloy material with gradient component proportion has become a key technical problem urgently to be solved in the material design of the metal hollow micro-lattice material in the future. SUMMARY
[0005] The purpose of the present application is to solve the above technical problems, and provide a preparation method of an alloy hollow micro-lattice material with gradient component proportion.
[0006] A preparation method of an alloy hollow micro-lattice material with gradient component proportion is carried out according to the following steps:
[0007] Step S1: surface pretreatment of the template of the metal hollow micro-lattice material to obtain product A; depositing a metal pre-plating layer on the product A by using surface deposition technology to obtain product B;
[0008] Step S2: preparing a multi-layer metal layer with multi-level alternating gradient deposition on the surface of the product B obtained in step S1 by controlling the system, and removing the product A to obtain product C; the multi-layer metal layer is nickel, iron, copper and cobalt, or tin and copper;
[0009] Step S3: subjecting the product C obtained in step S2 to thermal diffusion alloying treatment to obtain an alloy hollow micro-lattice material with gradient component ratio, which is a copper-tin alloy hollow micro-lattice material or a NiFeCuCo alloy hollow micro-lattice material.
[0010] Advantages of the present application:
[0011] (1) The present application is a preparation method of an alloy hollow micro-lattice material with gradient component ratio, which can prepare an alloy hollow micro-lattice material with gradient component ratio, and realizes the material design goal of gradient alloying of metal hollow micro-lattice materials;
[0012] (2) The preparation method is simple to operate, clear in process, safe and reliable in equipment, energy-saving and time-saving in preparation, and has good environmental affinity;
[0013] (3) The present application can be applied to various complex structures or even structural parts, greatly expanding the performance and application range of metal hollow micro-lattice materials;
[0014] (4) The gradient component ratio of the present application is flexible, the element composition is rich, and the alloy component selection is controllable.
[0015] The present application can obtain a preparation method of an alloy hollow micro-lattice material with gradient component ratio. BRIEF DESCRIPTION OF DRAWINGS
[0016] Figure 1 A preparation process flow chart of a NiFeCuCo alloy hollow micro-lattice material with gradient component ratio in Example 1 is shown;
[0017] Figure 2 A schematic diagram of the control system in the present application is shown;
[0018] Figure 3 A wall thickness control example curve of the alloy hollow micro-lattice material in the present application is shown;
[0019] Figure 4 A physical map of the NiFeCuCo alloy hollow micro-lattice material prepared in Example 1 is shown. DETAILED DESCRIPTION
[0020] Specific embodiment one: the present embodiment is a preparation method of an alloy hollow micro-lattice material with gradient component ratio, which is carried out according to the following steps:
[0021] Step S1: subjecting the template of the metal hollow micro-lattice material to surface pretreatment to obtain product A; using surface deposition technology to deposit a metal pre-plating layer on product A to obtain product B;
[0022] Step S2: preparing a multilayer metal layer with multiple alternating gradient deposition on the surface of product B obtained in step S1 by the control system, and removing product A to obtain product C; the multilayer metal layer is nickel, iron, copper and cobalt, or tin and copper;
[0023] As shown in Figure 3 Step S2, only one time controller and a threaded rod with Z axis are needed to control the height of product B immersed in the solution, so as to realize the thickness gradient change of the multilayer metal layer. The deposition thickness gradient of the plating layer on the surface of product B is related to the time of the immersion liquid and the immersion height of the sample. The time of the surface of product B at different heights in the liquid is different, and the deposition thickness of the plating layer is also different. The longer the time is, the thicker the thickness is. After repeatedly turning over product B, the gradient change of the proportion of metal elements at different heights is realized after depositing multiple metal layers on the surface.
[0024] Step S3: performing thermal diffusion alloying treatment on product C obtained in step S2 to obtain an alloy hollow micro-dot array material with a gradient component ratio, and the alloy hollow micro-dot array material with a gradient component ratio is a copper-tin alloy hollow micro-dot array material or a NiFeCuCo alloy hollow micro-dot array material.
[0025] The control system is a mechanical device considering the clamping and lifting motion of the experimental sample, mainly including a control console, a transmission mechanism and a fixing mechanism. The thickness control of the alloy hollow micro-dot array material is realized by controlling the switch of the control console, the rotating speed of the transmission mechanism and setting the process curve. The transmission process curve function is one of a linear function, a quadratic function, a power function and an exponential function.
[0026] Specific implementation method two: the difference between this embodiment and the specific implementation method one is that the template of the metal hollow micro-dot array material in step S1 is prepared by light-cured 3D printing.
[0027] The other steps are the same as those in the specific implementation method one.
[0028] Specific implementation method three: the difference between this embodiment and the specific implementation method one or two is that the template of the metal hollow micro-dot array material in step S1 is prepared by using 355 nm photosensitive resin.
[0029] The other steps are the same as those in the specific implementation method one or two.
[0030] Specific implementation method four: the difference between this embodiment and one of the specific implementation methods one to three is that the specific steps of surface pretreatment of the template of the metal hollow micro-dot array material in step S1 are as follows:
[0031] a) removing residual liquid resin: the template of the metal hollow micro-dot array material is immersed in an alcohol solution at a temperature of 20-30°C, soaked for 1-12 hours, and then washed with distilled water to obtain an experimental sample with the residual liquid resin removed;
[0032] b) alkaline degreasing: the experimental sample with the residual liquid resin removed is placed in solution D, ultrasonically cleaned at a temperature of 20-30°C for 20-60 minutes, and then washed with distilled water to obtain an experimental sample after alkaline degreasing; the solution D is composed of 10-30 g / L of sodium hydroxide, 1-30 g / L of sodium silicate, 10-40 g / L of trisodium phosphate, and 5-20 g / L of sodium carbonate, and the volume ratio of the sodium hydroxide, sodium silicate, trisodium phosphate, and sodium carbonate is (0.5-2) : (0.5-2) : (0.5-2) : (0.5-2);
[0033] c) sensitization: the experimental sample after alkaline degreasing is placed in a stannous chloride solution of 5-20 g / L, soaked at a temperature of 20-30°C for 10-20 minutes, and then washed with distilled water to obtain a sensitized experimental sample;
[0034] d) activation: the sensitized experimental sample is placed in a palladium chloride solution of 0.5-2 g / L, soaked at a temperature of 20-30°C for 15-30 minutes, and then washed with distilled water to obtain an activated experimental sample;
[0035] e) reduction: the activated experimental sample is placed in a sodium hypophosphite solution of 10-30 g / L, soaked at a temperature of 20-30°C for 3-5 minutes, and then washed with distilled water to obtain a reduced experimental sample;
[0036] f) weak etching: the reduced experimental sample is placed in a hydrochloric acid solution with a concentration of 10%, soaked at a temperature of 20-30°C for 5-10 seconds, and then washed with distilled water to obtain product A.
[0037] The other steps are the same as those in Embodiments One to Three.
[0038] Embodiment Five: the difference between this embodiment and one of Embodiments One to Four is that the surface deposition technique in step S1 is chemical plating, electroplating, ion plating, evaporation plating, or chemical vapor deposition.
[0039] The other steps are the same as those in Embodiments One to Four.
[0040] Embodiment Six: the difference between this embodiment and one of Embodiments One to Five is that the metal pre-plating layer in step S1 is 2-7 kinds of nickel, iron, cobalt, copper, chromium, aluminum, tin, silver, gold, and palladium.
[0041] The other steps are the same as Embodiment 1-5.
[0042] Embodiment 7: The difference between this embodiment and one of Embodiments 1-6 is that the control system in step S2 comprises a control console, a transmission mechanism and a fixing mechanism.
[0043] The other steps are the same as Embodiments 1-6.
[0044] Embodiment 8: The difference between this embodiment and one of Embodiments 1-7 is that the product A is removed by alkaline etching in step S2.
[0045] The other steps are the same as Embodiments 1-7.
[0046] Embodiment 9: The difference between this embodiment and one of Embodiments 1-8 is that the product A is removed by high-temperature calcination in step S2.
[0047] The other steps are the same as Embodiments 1-8.
[0048] Embodiment 10: The difference between this embodiment and one of Embodiments 1-9 is that the heat diffusion alloy treatment in step S3 is heating the product C to a temperature T and keeping the temperature T for 8-30 hours, and the temperature T=(80%-95%)T m , T m is the melting point of the metal with the lowest melting point in the multi-layer metal layer.
[0049] The other steps are the same as Embodiments 1-9.
[0050] The beneficial effects of the present application are verified by the following examples:
[0051] Example 1: As shown in the following, a preparation method of an alloy hollow micro-lattice material with a gradient composition ratio is carried out according to the following steps: Figure 1
[0052] Step S1: A 355 nm photosensitive resin is used as a material to prepare a metal hollow micro-lattice material template by a light-cured 3D printer, and the internal node number is 8x8x8 structure; the metal hollow micro-lattice material template is surface pretreated to obtain product A;
[0053] The specific steps of surface pretreatment of the metal hollow micro-lattice material template in step S1 are as follows:
[0054] a) removing residual liquid resin: the template of the metal hollow micro-dot array material is immersed in the alcohol solution at the temperature of 25℃, and after soaking for 4h, it is cleaned by distilled water to obtain the experimental sample with the removed residual liquid resin;
[0055] b) removing oil by alkali: the experimental sample with the removed residual liquid resin is placed in solution D, and it is cleaned by ultrasonic cleaning at the temperature of 25℃ for 30min, and then by distilled water to obtain the experimental sample after removing oil by alkali; the solution D is composed of 12g / L of sodium hydroxide, 8g / L of sodium silicate, 20g / L of trisodium phosphate and 7g / L of sodium carbonate, and the volume ratio of sodium hydroxide, sodium silicate, trisodium phosphate and sodium carbonate is 1:1:1:1;
[0056] c) sensitization: the experimental sample after removing oil by alkali is placed in the stannous chloride solution of 10g / L, and it is soaked at the temperature of 25℃ for 10min, and then cleaned by distilled water to obtain the experimental sample after sensitization;
[0057] d) activation: the experimental sample after sensitization is placed in the palladium chloride solution of 0.7g / L, and it is soaked at the temperature of 25℃ for 20min, and then cleaned by distilled water to obtain the experimental sample after activation;
[0058] e) reduction: the experimental sample after activation is placed in the sodium hypophosphite solution of 15g / L, and it is soaked at the temperature of 25℃ for 5min, and then cleaned by distilled water to obtain the experimental sample after reduction;
[0059] f) weak etching: the experimental sample after reduction is placed in the hydrochloric acid solution with the concentration of 10%, and it is soaked at the temperature of 25℃ for 10s, and then cleaned by distilled water to obtain product A;
[0060] The product A is placed in the electroless nickel plating solution with the temperature of 40℃ and pH of 10, which is composed of 20g / L of nickel sulfate, 40g / L of sodium pyrophosphate, 20g / L of sodium citrate and 2.5g / L of sodium hydroxide, and the volume ratio of nickel sulfate, sodium pyrophosphate, sodium citrate and sodium hydroxide is 1:1:1:1, to pre-plate a nickel layer to obtain product B.
[0061] Step S2: a metal layer with the gradient deposition of nickel, iron, copper and cobalt is prepared on the surface of the product B obtained in step S1 by controlling the system (as shown in Figure 2 ), and then the product A is removed by alkali etching to obtain product C.
[0062] Step S3: the product C obtained in step S2 is heat-diffused and alloyed at 800℃ for 20h to obtain the NiFeCuCo alloy hollow micro-dot array material with gradient component ratio, as shown in Figure 4 .
[0063] Embodiment 2: A preparation method of an alloy hollow micro-lattice material with gradient component ratio, which is carried out according to the following steps:
[0064] Step S1: A two-way concave honeycomb structure template of a metal hollow micro-lattice material is prepared by using a photosensitive resin with a wavelength of 355 nm as a material and using a light-cured 3D printer, and the internal nodes of the template are in a structure of 12x12x12;
[0065] The specific steps of surface pretreatment of the template of the metal hollow micro-lattice material in step S1 are as follows:
[0066] a) Removing residual liquid resin: The printed resin template is immersed in an alcohol solution at a temperature of 25°C, soaked for 10 hours, and then washed with distilled water to obtain an experimental sample with residual liquid resin removed;
[0067] b) Alkaline degreasing: The experimental sample with residual liquid resin removed is placed in solution D and ultrasonically cleaned at a temperature of 25°C for 60 minutes, and then washed with distilled water to obtain an experimental sample after alkaline degreasing; the solution D is composed of 12 g / L of sodium hydroxide, 8 g / L of sodium silicate, 20 g / L of trisodium phosphate, and 20 g / L of sodium carbonate, and the volume ratio of sodium hydroxide, sodium silicate, trisodium phosphate, and sodium carbonate is 1:1:1:1;
[0068] c) Sensitization: The experimental sample after alkaline degreasing is placed in a 20 g / L stannous chloride solution and soaked at a temperature of 25°C for 20 minutes, and then washed with distilled water to obtain a sensitized experimental sample;
[0069] d) Activation: The sensitized experimental sample is placed in a 2 g / L palladium chloride solution and soaked at a temperature of 25°C for 30 minutes, and then washed with distilled water to obtain an activated experimental sample;
[0070] e) Reduction: The activated experimental sample is placed in a 15 g / L sodium hypophosphite solution and soaked at a temperature of 25°C for 5 minutes, and then washed with distilled water to obtain a reduced experimental sample;
[0071] f) Weak etching: The reduced experimental sample is placed in a 10% hydrochloric acid solution at a temperature of 25°C for 10 seconds, and then washed with distilled water to obtain product A;
[0072] The product A is pre-plated with a nickel layer in a chemical nickel plating solution with a temperature of 40℃, pH of 10, and consisting of 20g / L nickel sulfate, 40g / L sodium pyrophosphate, 20g / L sodium citrate and 2.5g / L sodium hydroxide, with a volume ratio of 1:1:1:1 for the nickel sulfate, sodium pyrophosphate, sodium citrate and sodium hydroxide, to obtain product B.
[0073] Step S2: a metal layer with gradient deposition of tin and copper is prepared on the surface of the product B obtained in step S1 by controlling the system (as shown in Figure 2 Step S3: the product C obtained in step S2 is heat-diffusion alloyed at 600℃ for 15h to obtain a copper-tin alloy hollow micro-lattice material with gradient composition ratio.
[0074] Step S3: the product C obtained in step S2 is heat-diffusion alloyed at 600℃ for 15h to obtain a copper-tin alloy hollow micro-lattice material with gradient composition ratio.
Claims
1. A method for preparing an alloy hollow microlattice material with gradient composition ratio, characterized in that... The preparation method is carried out according to the following steps: Step S1: Pre-treat the surface of the template of the metal hollow microlattice material to obtain product A; A metal pre-plating layer was deposited onto product A using surface deposition technology to obtain product B; Step S2: By controlling the system, a multilayer metal layer with alternating gradient deposition is prepared on the surface of product B obtained in step S1, and product A is removed to obtain product C; the multilayer metal layer is nickel, iron, copper and cobalt, or tin and copper; In step S2, only a time controller and a threaded rod with a Z-axis are needed to control the height of product B immersed in the solution, which can achieve the thickness gradient change of multiple metal layers. The deposition thickness gradient of the coating on the surface of product B is related to the immersion time in the liquid and the immersion height of the sample. The product B surface at different heights has different time in the liquid, and the thickness of the deposited coating is also different. The longer the time, the thicker the coating. By repeatedly flipping product B and depositing multiple metal layers on the surface, the gradient change of the metal element ratio at different heights is achieved. Step S3: The product C obtained in step S2 is subjected to thermal diffusion alloying treatment to obtain an alloy hollow microlattice material with a gradient composition ratio. The alloy hollow microlattice material with a gradient composition ratio is a copper-tin alloy hollow microlattice material or a NiFeCuCo alloy hollow microlattice material.
2. The method for preparing an alloy hollow microlattice material with a gradient composition ratio according to claim 1, characterized in that... The template for the hollow metal microlattice material mentioned in step S1 is prepared by photopolymerization 3D printing.
3. A method for preparing an alloy hollow microlattice material with a gradient composition ratio according to claim 1 or 2, characterized in that... In step S1, the template for preparing the metal hollow microlattice material is a 355nm photosensitive resin.
4. The method for preparing an alloy hollow microlattice material with a gradient composition ratio according to claim 1, characterized in that... The specific steps for surface pretreatment of the template of the metal hollow micro-lattice material in step S1 are as follows: a) Removal of residual liquid resin: The template of the metal hollow micro-lattice material is immersed in an alcohol solution at a temperature of 20~30℃ for 1~12 hours, and then washed with distilled water to obtain an experimental sample with the residual liquid resin removed. b) Alkaline degreasing: The experimental sample after removing residual liquid resin is placed in solution D and ultrasonically cleaned at a temperature of 20~30℃ for 20min~60min, and then washed with distilled water to obtain the experimental sample after alkaline degreasing; the solution D is composed of 10g / L~30g / L sodium hydroxide, 1g / L~30g / L sodium silicate, 10g / L~40g / L trisodium phosphate and 5g / L~20g / L sodium carbonate, and the volume ratio of sodium hydroxide, sodium silicate, trisodium phosphate and sodium carbonate is (0.5~2):(0.5~2):(0.5~2):(0.5~2); c) Sensitization: The experimental sample after alkaline degreasing is placed in a 5 g / L~20 g / L stannous chloride solution and soaked at a temperature of 20~30℃ for 10 min~20 min, and then washed with distilled water to obtain the sensitized experimental sample. d) Activation: The sensitized experimental sample was placed in a 0.5 g / L to 2 g / L palladium chloride solution and soaked at 20 to 30 °C for 15 to 30 minutes. Then it was washed with distilled water to obtain the activated experimental sample. e) Reduction: The activated experimental sample was placed in a sodium hypophosphite solution of 10 g / L to 30 g / L and soaked at a temperature of 20 to 30°C for 3 to 5 minutes. Then it was washed with distilled water to obtain the reduced experimental sample. f) Weak corrosion: The reduced experimental sample was placed in a 10% hydrochloric acid solution and soaked for 5 to 10 seconds at a temperature of 20 to 30°C. Then it was washed with distilled water to obtain product A.
5. The method for preparing an alloy hollow microlattice material with a gradient composition ratio according to claim 1, characterized in that... The surface deposition technique described in step S1 is chemical plating or electroplating.
6. The method for preparing an alloy hollow microlattice material with a gradient composition ratio according to claim 1, characterized in that... The metal pre-plating layer mentioned in step S1 is 2 to 7 of the following: nickel, iron, cobalt, copper, chromium, aluminum, tin, silver, gold and palladium.
7. The method for preparing an alloy hollow microlattice material with a gradient composition ratio according to claim 1, characterized in that... The control system described in step S2 includes a control console, a transmission mechanism, and a fixing mechanism.
8. The method for preparing an alloy hollow microlattice material with gradient composition ratio according to claim 1, characterized in that... In step S2, product A is removed by alkaline etching.
9. The method for preparing an alloy hollow microlattice material with a gradient composition ratio according to claim 1, characterized in that... In step S2, product A is removed by high-temperature calcination.
10. The method for preparing an alloy hollow microlattice material with a gradient composition ratio according to claim 1, characterized in that... The thermal diffusion alloying treatment described in step S3 involves heating product C to temperature T and holding it at temperature T for 8 to 30 hours, where temperature T = (80% to 95%)T. m T m It is the melting point of the metal with the lowest melting point in the multilayer metal structure.
Citation Information
Patent Citations
Ultra-light hollow pipe microarray metal material built by adopting template method and preparation method thereof
CN103805972A
Preparation method of ultralight high-entropy alloy with micro-lattice structure
CN110344040A